Design of a Heartbeat Detector Using a Photopletysmograph Method Based on an ATMega328 Microcontroller - Lukito, Pandu; Supardi, I Wayan; Ratini, Ni Nyoman (BULETIN FISIKA; Vol 24 No 2 (2023): BULETIN FISIKA August Edition, 2023)
The heart is one of the human organs who has important role to pumping the blood. Heart rate monitoring needs to do for knowing person's heart health any time. In this research, a heart rate detector using the photopletysmograph method based on the ATMega328 microcontroller has been successfully made using reflection mode. The design of this tool uses a photodiode sensor as a light receiver from infrared LEDs. The measurement results are processed using Arduino uno and displayed on the LCD. The reference tool used to calibrate this heart rate detector is the LK-87 pulse oximeter. The test results show that the tool is feasible to use with an accuracy level of 98.32% and an average error of 1.60%.